Structured programming learning through the use of information channeling of information using servo technology education and paintings in their steps fractals (2016)
ABSTRACT: Educational robotic in education is a tool for teachers and a learning strategy in the classroom. Keeping in mind that each student has a different way to get the information in the knowledge acquisition of any topic, in this project the information channelings will be use according to the visual and logic model of multiple learning styles (EMMA). In this research some practices were designed, implemented and proven for the subject Structured Design of algorithm for the use of robotics helping in the management and comprehension of controlled structures like cycles and controlled structures. Students comprehended better by using this technique which includes robotics, due to they not only learned the instructions to execute these procedures but they experimented the visualization programming these instructions into robots. Using the simulator platform for the robot BYOB, which is a Scratch program, with this technique, it could be possible to prove that students comprehended and assimilated the use and management of structures besides they learned other kind of programming and the manipulation of robots. The use of robotics awakes in students the need for learn beyond the subject. This technique creates in the student an active thought with the need for learning more reaching a self- study learning and paintings in their steps fractals.